1996
DOI: 10.1074/jbc.271.7.3453
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted Signaling in a Mutant J2E Cell Line That Shows Enhanced Viability, but Does Not Proliferate or Differentiate, with Erythropoietin

Abstract: The immature erythroid J2E cell line proliferates and terminally differentiates following erythropoietin stimulation. In contrast, the mutant J2E-NR clone does not respond to erythropoietin by either proliferating or differentiating. Here we show that erythropoietin can act as a viability factor for both the J2E and J2E-NR lines, indicating that erythropoietin-initiated maturation is separable from the prevention of cell death. The inability of J2E-NR cells to mature in response to erythropoietin was not due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 55 publications
6
44
0
Order By: Relevance
“…Moreover, epo-initiated viability and proliferation were inhibited in these cells (Figure 5b,c). Since J2E-NR cells do not proliferate or di erentiate, but remain alive, in response to epo (Klinken and Nicola, 1990;Tilbrook et al, 1996a), a dose response curve was generated to test the e ects of the D321 receptor on the viability of J2E-NR cells. Figure 5d shows that epo-induced viability of cells with D321 receptor was enhanced compared with J2E-NR cells.…”
Section: Dominant Effect Of Mutated Epo Receptorsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, epo-initiated viability and proliferation were inhibited in these cells (Figure 5b,c). Since J2E-NR cells do not proliferate or di erentiate, but remain alive, in response to epo (Klinken and Nicola, 1990;Tilbrook et al, 1996a), a dose response curve was generated to test the e ects of the D321 receptor on the viability of J2E-NR cells. Figure 5d shows that epo-induced viability of cells with D321 receptor was enhanced compared with J2E-NR cells.…”
Section: Dominant Effect Of Mutated Epo Receptorsmentioning
confidence: 99%
“…These phosphorylated tyrosines act as docking sites for signaling proteins including Signal Transducer and Activator of Transcription 5 (STAT 5), the p85 subunit of phosphatidylinositol 3-kinase (PI3-kinase) and phosphatases SHP-1 and SHP-2 (Damen et al, 1995a,b;Gobert et al, 1996;Klingmuller et al, 1995Klingmuller et al, , 1996Klingmuller et al, , 1997Penta and Sawyer, 1995;Quelle et al, 1996;Sharlow et al, 1997;Tauchi et al, 1995Tauchi et al, , 1996Yi et al, 1995). Although Shc and Grb2 bind to the epo receptor and stimulate the Ras/Raf/MAP-kinase pathway (Barber et al, 1997;Bittorf et al, 1994;Carroll et al, 1991;Cutler et al, 1993;Gobert et al, 1995;He et al, 1995;Miura et al, 1994b;Tilbrook et al, 1996a;Torti et al, 1992), their precise binding locations on the receptor have not been identi®ed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on Friend virus-infected erythroid cells and the epo-dependent HCD-57 line have shown that epo retards DNA breakdown and maintains cell viability Bondurant, 1988, 1990;Spivak et al, 1991). Our recent studies have indicated that distinct epo-induced signalling pathways may exist in cells which lead to cell division, maturation and maintenance of viability (Tilbrook et al, 1996a). In addition, IL-2, IL-3 and GM ± CSF transmit signals that promote cell survival, independent of initiating cell division (Okuda et al, 1994;Inhorn et al, 1995;Kinoshita et al, 1995;Boise et al, 1995).…”
Section: Introductionmentioning
confidence: 99%